Molybdenum powder with high specific surface area, preparation method thereof and ceramic metallization slurry
Through hot pressing and crushing and powder making treatment, the specific surface area of molybdenum powder is improved, and the specific surface area of traditional molybdenum powder is solved, the bonding strength between the ceramic matrix and metal is enhanced, and the preparation process is simplified, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411587972.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-11
AI Technical Summary
The specific surface area of existing molybdenum powder is too low, which affects the bonding strength and high temperature stability between the ceramic matrix and metal. The traditional preparation method is complex in operation and high energy consumption, making it not suitable for large-scale industrial production.
The specific surface area of molybdenum powder is increased by hot pressing and crushing and powder making treatment. The specific steps include vacuum hot pressing of the molybdenum powder raw material at 900-1100°C for 5-30 minutes to obtain a hot pressing blank, then ball milling, and finally obtain a high specific surface area molybdenum powder with a particle size distribution of 1-20 μm through sieving.
Molybdenum powder with a specific surface area of more than three times higher than traditional molybdenum powder is obtained, which enhances the interface bonding strength between the ceramic matrix and the metal, simplifies the preparation process, and is suitable for industrial production.
Smart Images

Figure CN119588930A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of metal powder preparation, and specifically provides a high specific surface area molybdenum powder and a preparation method thereof and a ceramic metallization slurry. Background Art
[0002] As an important metal material, molybdenum powder has a wide range of application prospects. Ceramic-metal connectors are widely used in the fields of electronics, semiconductor packaging, etc. Molybdenum powder, as a refractory metal powder, can be used as a transition layer between ceramic matrix and metal to improve the bonding strength between ceramic and metal and ensure the high temperature stability and thermal conductivity between the two.
[0003] The traditional methods for preparing molybdenum powder mainly include: plasma reduction method, molybdenum chloride steam hydrogen reduction method, molybdenum chloride pyrolysis method, molybdenum trioxide evaporation reduction method, uniform precipitation-reduction method, etc. However, the molybdenum powder prepared by the above conventional methods is a solid single-particle molybdenum powder with no porous structure inside the particles and a low specific surface area. The low specific surface area of molybdenum powder is not conducive to its use as a transition layer between ceramic matrix and metal. This is because: low specific surface area of molybdenum powder means that the contact area between its particles is small. The limited contact area will directly affect the bonding strength of the transition layer. At the same time, it may be difficult to achieve the ideal density during the sintering process, resulting in pores and defects in the transition layer, thereby affecting the stability and reliability of the overall structure.
[0004] CN117324619A discloses a molybdenum powder and a preparation method thereof, wherein the molybdenum powder is agglomerated particles formed by agglomeration of nano-scale molybdenum powder, and the interior of the agglomerated particles is a loose porous structure; the preparation method of the molybdenum powder comprises: subjecting large-particle molybdenum powder or molybdenum blocks and an activator (such as ethanol and oleic acid) to three-stage electric ball milling, and controlling the operating conditions of each stage to obtain the molybdenum powder of the desired structure. However, the operating conditions of the preparation method are complex, the energy consumption is too high, the introduced activator affects the application performance of the molybdenum powder, the inert gas cost investment is high, the preparation time is long, and it is not conducive to industrial large-scale production.
[0005] Therefore, it is necessary to develop new methods for industrially and efficiently preparing high specific surface area molybdenum powder. Summary of the invention
[0006] In view of the above problems existing in the prior art, the purpose of the present application is to provide a molybdenum powder with a high specific surface area and a preparation method thereof and a ceramic metallization slurry. The preparation method of the present application has a simple process and can effectively increase the specific surface area compared with the molybdenum powder raw material used to obtain a molybdenum powder with a high specific surface area.
[0007] In a first aspect, the present application provides a method for preparing high specific area molybdenum powder, the method comprising:
[0008] (1) Hot pressing treatment: 1 The molybdenum powder raw material is placed in a mold, and hot-pressed at 900-1100° C. for 5-30 minutes to obtain a hot-pressed blank;
[0009] (2) Crushing and pulverizing: The hot pressed green body is crushed and pulverized to obtain a specific surface area A 2 High specific area molybdenum powder, where A 1 <A 2 .
[0010] In the method provided by the present application, by subjecting the molybdenum powder raw material to rapid hot pressing and crushing and powdering treatment, a high specific surface area molybdenum powder can be obtained, and the molybdenum powder has a loose porous structure; compared with molybdenum powder with a solid structure, the porous structure provides a larger contact area, which is conducive to enhancing the interface bonding strength between the ceramic matrix and the metal and ensuring the bonding stability between the two. In addition, the method of the present application is simple to operate and suitable for industrial implementation.
[0011] In some embodiments of the present application, the specific surface area A of the molybdenum powder raw material 1 0.3~0.8m 2 / g, the specific surface area A of the high specific area molybdenum powder 2 With A 1 Satisfies the following relationship: A 2 / A 1 >3.
[0012] In some embodiments of the present application, the Fischer-Lehr particle size of the molybdenum powder raw material is 20-500 nm, and the purity of the molybdenum powder raw material is ≥99%.
[0013] In some embodiments of the present application, the hot pressing treatment is a vacuum hot pressing treatment, and the applied pressure is 5 to 60 MPa. If the pressure is too low, the driving force may be too small to promote grain growth and the specific area cannot be effectively increased. If the pressure is too high, the grains may grow excessively, making the molybdenum powder particles coarse, which may reduce its specific surface area and be unfavorable for subsequent crushing and powdering.
[0014] Furthermore, during the hot pressing treatment, the applied pressure is 10 to 50 MPa.
[0015] In some embodiments of the present application, the crushing and pulverizing process is a ball milling process, the ball-to-material ratio is (5-100):1, and the ball milling time is 12-50 hours.
[0016] In some embodiments of the present application, the method further includes: (3) screening, screening the product after the crushing and pulverizing process to obtain a high specific area molybdenum powder with a particle size distribution of 1 to 20 μm. By removing coarse particles in the molybdenum powder product through screening and controlling the particle size distribution within this range, the stability of the slurry prepared by the molybdenum powder and the uniformity when coating to form a transition layer can be improved.
[0017] In some embodiments of the present application, the specific surface area A of the high specific area molybdenum powder is 2 1.8~3m 2 In this way, on the one hand, the transition layer prepared with the molybdenum powder has a high bonding strength with the ceramic substrate and the coating has a high density, and on the other hand, the possibility of excessive sintering of the slurry due to an excessively high specific surface area, which affects the surface porosity and roughness, can be reduced.
[0018] In a second aspect, the present application provides a high specific area molybdenum powder prepared by the method described in the first aspect of the present application.
[0019] In a third aspect, the present application provides a ceramic metallization slurry comprising a solid powder and an organic binder, wherein the solid powder comprises molybdenum powder and oxide, and the molybdenum powder is the high specific area molybdenum powder described in the second aspect of the present application.
[0020] After the ceramic metallization slurry of the present application is coated and sintered on the ceramic substrate, the formed non-metal phase is evenly distributed, which is beneficial to improving the bonding strength between the transition layer and the substrate.
[0021] In some embodiments of the present application, the oxide is at least one of manganese oxide, aluminum oxide and silicon dioxide, and the organic binder is pinene alcohol and / or ethyl cellulose.
[0022] In some embodiments of the present application, in the solid powder, the mass content of the molybdenum powder is 65% to 85%, and the mass content of the oxide is 15% to 35%.
[0023] In some embodiments of the present application, the amount of the organic binder added is 30 to 40 parts by weight relative to 100 parts by weight of the solid powder.
[0024] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0026] Figure 1This is a SEM image of the high specific surface area molybdenum powder prepared in Example 1;
[0027] Figure 2 This is a SEM image of a cross section of the metallized ceramic substrate prepared in Example 1;
[0028] Figure 3 This is a SEM image of the high specific surface area molybdenum powder prepared in Example 2;
[0029] Figure 4 This is a SEM image of a cross section of the metallized ceramic substrate prepared in Example 2;
[0030] Figure 5 This is the SEM image of the molybdenum powder prepared in Comparative Example 1;
[0031] Figure 6 This is the SEM image of the molybdenum powder prepared in Comparative Example 2;
[0032] Figures 7-8 The SEM images of the molybdenum powder (alloyed) prepared in Comparative Example 3 at different magnifications;
[0033] Fig. 9 This is the SEM image of the molybdenum powder prepared in Comparative Example 4. DETAILED DESCRIPTION
[0034] The following describes the implementation of the present application in detail. The implementation described below is exemplary and is only used to explain the present application, and cannot be understood as limiting the present application.
[0035] The "range" disclosed in the present application is defined in the form of a lower limit and / or an upper limit, and a given range is defined by selecting a lower limit and / or an upper limit. The range defined in this way can be inclusive or exclusive of end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form an unclearly recorded range, and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, each separately disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0036] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0037] The first aspect of the present application provides a method for preparing high specific area molybdenum powder, the method comprising:
[0038] (1) Hot pressing treatment:1 The molybdenum powder raw material is placed in a mold, and hot-pressed at 900-1100° C. for 5-30 minutes to obtain a hot-pressed blank;
[0039] (2) Crushing and pulverizing: The hot pressed green body is crushed and pulverized to obtain a specific surface area A 2 High specific area molybdenum powder, where A 1 <A 2 .
[0040] According to the method of the present application, the molybdenum powder raw material can be selected from various solid molybdenum powders. After the hot pressing treatment and crushing and powder making treatment, a loose porous structure can be formed in the molybdenum powder.
[0041] In some embodiments, the specific surface area A of the molybdenum powder raw material 1 Can be 0.3~0.8m 2 / g, for example 0.30m 2 / g, 0.40m 2 / g, 0.42m 2 / g, 0.45m 2 / g, 0.46m 2 / g, 0.48m 2 / g, 0.50m 2 / g, 0.51m 2 / g, 0.60m 2 / g, 0.75m 2 / g, 0.80m 2 / g, etc.
[0042] In some embodiments, the molybdenum powder raw material may have a Fisher particle size of 20 nm to 500 nm, such as 20 nm, 45 nm, 100 nm, 200 nm, 260 nm, 300 nm, 320 nm, 350 nm, 400 nm, etc. Further, the molybdenum powder raw material has a Fisher particle size of 100 to 300 nm.
[0043] In some embodiments, the purity of the molybdenum powder raw material is ≥ 99%. The higher the purity, the more conducive it is to forming a stronger chemical bond, thereby improving the bonding strength of the transition layer.
[0044] According to the method of the present application, the molybdenum powder raw material can be obtained commercially or prepared by methods well known in the art, such as but not limited to plasma hydrogen reduction method, electric pulse discharge method, microwave plasma method, etc.
[0045] In step (1), the processing temperature of the hot pressing treatment is 900-1100°C, such as 900°C, 920°C, 930°C, 955°C, 970°C, 980°C, 985°C, 990°C, 1000°C, 1050°C, 1100°C, etc. If the temperature of the hot pressing treatment is too low, an effective driving force cannot be provided and a porous structure cannot be formed. If the temperature of the hot pressing treatment is too high, the molybdenum powder will be heated and dense, resulting in alloying.
[0046] The hot pressing treatment time can be 5 to 30 minutes, such as 8 minutes, 10 minutes, 12 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, etc. If the hot pressing treatment time is too short, it is not enough to obtain a high specific surface area by hot pressing molding. If the hot pressing treatment time is too long, the molybdenum powder will be further densified and a porous structure cannot be effectively formed.
[0047] In step (1), the hot pressing treatment may be a vacuum hot pressing treatment.
[0048] In some embodiments, the pressure applied during the hot pressing process may be 5-60 MPa, such as 5 MPa, 10 MPa, 15 MPa, 20 MPa, 25 MPa, 30 MPa, 40 MPa, 50 MPa, 60 MPa, etc. Preferably, the pressure applied during the hot pressing process is 10-50 MPa.
[0049] According to the method of the present application, molybdenum powder with a high specific surface area can be obtained by crushing and powdering the hot pressed blank.
[0050] In step (2), the crushing and powdering treatment may be performed by, for example, ball milling, grinding, vibration milling, air flow milling, etc.
[0051] In some embodiments, the crushing and pulverizing process is a ball milling process.
[0052] In step (2), the ratio of balls to materials in the ball milling process can be selected according to the size of the hot pressed green sheet. Generally, the larger the hot pressed green sheet is, the higher the ratio of balls to materials is. According to some embodiments, the ratio of balls to materials in the ball milling process can be (5-100):1, for example, 1:1, 5:1, 10:1, 15:1, 20:1, 30:1, 50:1, 80:1, etc. Further, the ratio of balls to materials in the ball milling process is (5-50):1.
[0053] In some embodiments, the ball milling time is 12 to 50 h, for example, 12 h, 15 h, 20 h, 25 h, 30 h, 36 h, 40 h, 45 h, 48 h, etc.
[0054] In some embodiments, the method further comprises: (3) screening the product after the crushing and pulverizing process to obtain a high specific surface area molybdenum powder with a particle size distribution of 1 to 20 μm. As some examples, the particle size distribution of the high specific surface area molybdenum powder can be 1 to 5 μm, 1 to 3 μm, 2 to 8 μm, 2 to 10 μm, etc.
[0055] According to some specific embodiments, the method for preparing high specific area molybdenum powder in the present application includes the following process:
[0056] The molybdenum powder raw material is loaded into a graphite mold, and placed in a hot pressing furnace loading platform for rapid vacuum hot pressing treatment. During the process, a pressure of 5 to 60 MPa is applied to the upper and lower ends of the graphite mold, the hot pressing temperature is 900 to 1100°C, the pressure is maintained for 5 to 30 minutes, and the temperature is reduced to obtain a hot pressed blank;
[0057] The hot pressed green sheet is placed in a dry ball mill, the ball-to-material ratio is controlled to be (5-100):1, and the ball mill is performed for 12-50 hours to fully crush the hot pressed green sheet;
[0058] The ball milled product is sieved to obtain high specific surface area molybdenum powder with a certain particle size distribution.
[0059] The second aspect of the present application provides a high specific surface area molybdenum powder prepared by the method described in the first aspect of the present application. The high specific surface area molybdenum powder is sliced by FIB and observed by scanning electron microscope (SEM), and has a loose porous structure.
[0060] As described above, the method of the present application can effectively increase the specific surface area of the molybdenum powder raw material. In some embodiments, the specific surface area A of the high specific area molybdenum powder is 2 The specific surface area A of molybdenum powder raw material 1 Satisfy the relationship: A 2 / A 1 >3, preferably A 2 / A 1 >3.3.
[0061] In some embodiments, the specific surface area of the high specific surface area molybdenum powder is 1.8 to 3 m 2 / g, for example 1.90m 2 / g, 2.05m 2 / g, 2.11m 2 / g, 2.13m 2 / g, 2.25m 2 / g, 2.34m 2 / g, 2.45m 2 / g, 2.50m 2 / g, 2.55m 2 / g, 2.60m 2 / g, etc.
[0062] The high specific surface area molybdenum powder of the present application can be used to prepare a metallization transition layer of a ceramic substrate, which is beneficial to enhancing the interface bonding strength between the ceramic matrix and the metal.
[0063] The third aspect of the present application provides a ceramic metallization slurry comprising a solid powder and an organic binder, wherein the solid powder comprises molybdenum powder and oxide, and the molybdenum powder is the high specific area molybdenum powder described in the second aspect of the present application.
[0064] In some embodiments, the oxide is selected from at least one of manganese oxide, aluminum oxide and silicon dioxide. Preferably, the oxide is manganese oxide, aluminum oxide and silicon dioxide, and the mass ratio of manganese oxide, aluminum oxide and silicon dioxide is 1: (1.1-1.5): (0.6-0.9).
[0065] In some embodiments, the organic binder is selected from terpineol (eg, α-terpineol) and / or ethyl cellulose. Preferably, the organic binder is α-terpineol and ethyl cellulose, and the mass ratio of α-terpineol to ethyl cellulose is 1:(0.1-0.3).
[0066] In some embodiments, in the solid powder, the mass content of the molybdenum powder is 65% to 85%, for example, 68%, 75%, 80%, 85%, etc.; the mass content of the oxide is 15% to 35%, for example, 32%, 25%, 20%, 15%, etc.
[0067] In some embodiments, the organic binder is 30 to 40 parts by weight, such as 30 parts by weight, 32 parts by weight, 35 parts by weight, 40 parts by weight, etc., relative to 100 parts by weight of the solid powder.
[0068] The present application does not particularly limit the preparation method of the ceramic metallization slurry, as long as the components can be evenly dispersed, for example, molybdenum powder, oxide and organic binder can be evenly mixed in a graphite stirrer using shear force to obtain the ceramic metallization slurry. As an example, the ceramic metallization slurry can be used to prepare a Langmuir probe.
[0069] The ceramic metallization slurry of the present application is coated and sintered on a ceramic substrate to form a coating. In the formed coating, the non-metallic phase and the metal phase are evenly distributed, and there is a high contact area and bonding strength between the two and between the coating and the ceramic substrate.
[0070] In the present application, the ceramic substrate is, for example but not limited to, an alumina substrate or a zirconia substrate. Generally, the coating (ie, transition layer) formed by the ceramic metallization slurry may have a thickness of 20 to 40 μm, such as 20 μm, 25 μm, 30 μm, etc.
[0071] In some embodiments, the sintering temperature may be 1400-1500° C., and the sintering time may be 8-10 hours. In addition, the sintering may be performed in a reducing atmosphere (eg, hydrogen).
[0072] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application.
[0073] In the following examples and comparative examples,
[0074] The BET specific surface area was measured by a dynamic reference method using a specific surface area analyzer (model: BET 3H-2000A).
[0075] The cross-sectional morphology of the molybdenum powder product was observed by focused ion double beam microscopy (FIB-SEM), and the cross-sectional morphology of the metal ceramic was observed by scanning electron microscopy (SEM).
[0076] Examples 1 to 7 are used to illustrate the high specific surface area molybdenum powder and the preparation method thereof of the present application.
[0077] Example 1
[0078] The particle size of the quartz crystal is 300nm and the specific surface area is 0.46m 2 / g, 99.0% purity molybdenum powder is used as the initial raw material. The molybdenum powder raw material is loaded into a graphite mold, and placed in a hot pressing furnace loading platform for rapid vacuum hot pressing treatment. During this process, a pressure of 40MPa is applied to the upper and lower ends of the graphite mold, the hot pressing temperature is 1000°C, the holding time is 10min, and then the temperature is reduced to obtain a hot pressed blank.
[0079] The hot pressed blank and the grinding balls were put into a ball mill for ball milling, with a ball-to-material ratio of 10:1 and a ball milling time of 48 hours. The ball milled product was sieved to obtain a molybdenum powder product with a particle size distribution of 1 to 5 μm, which was recorded as molybdenum powder M1.
[0080] The specific surface area of the molybdenum powder M1 obtained was 2.26 m 2 / g, which is a high specific surface area molybdenum powder. The cross-sectional morphology was observed by FIB sectioning. The results are as follows Figure 1 As shown in the figure, it can be seen that the interior of the molybdenum powder M1 has a loose porous structure.
[0081] Example 2
[0082] The particle size of the quartz crystal is 100 nm and the specific surface area is 0.51 m 2 / g, 99.5% purity molybdenum powder as the initial raw material. The molybdenum powder raw material is loaded into a graphite mold, and placed in a hot pressing furnace loading platform for rapid vacuum hot pressing treatment. During this process, a pressure of 20MPa is applied to the upper and lower ends of the graphite mold, the hot pressing temperature is 1050℃, the holding time is 15min, and then the temperature is reduced to obtain a hot pressed blank.
[0083] The hot pressed blank and the grinding balls were put into a ball mill for ball milling, with a ball-to-material ratio of 20:1 and a ball milling time of 36 hours. The ball milled product was sieved to obtain a molybdenum powder product with a particle size distribution of 1 to 3 μm, which was recorded as molybdenum powder M2.
[0084] After testing, the specific surface area of molybdenum powder M2 is 2.34m 2 / g, which is a high specific surface area molybdenum powder. The cross-sectional morphology was observed by FIB sectioning. The results are as follows Figure 3 As shown in the figure, it can be seen that the interior of the molybdenum powder M2 has a loose porous structure.
[0085] Example 3
[0086] The particle size of the quartz crystal is 300nm and the specific surface area is 0.46m 2 / g, 99.0% purity molybdenum powder is used as the initial raw material. The molybdenum powder raw material is loaded into a graphite mold, and placed in a hot pressing furnace loading platform for rapid vacuum hot pressing treatment. During this process, a pressure of 40MPa is applied to the upper and lower ends of the graphite mold, the hot pressing temperature is 1100°C, the holding time is 10min, and the hot pressed blank is obtained after cooling.
[0087] The hot pressed blank and the grinding balls were put into a ball mill for ball milling, with a ball-to-material ratio of 10:1 and a ball milling time of 48 hours. The ball milled product was sieved to obtain a molybdenum powder product with a particle size distribution of 2 to 10 μm, which was recorded as molybdenum powder M3.
[0088] After testing, the specific surface area of molybdenum powder M3 is 2.12m 2 / g. The cross-sectional morphology was observed by FIB sectioning, and the interior of molybdenum powder M3 was a loose porous structure.
[0089] Example 4
[0090] The particle size of the quartz crystal is 300nm and the specific surface area is 0.46m 2 / g, 99.0% purity molybdenum powder is used as the initial raw material. The molybdenum powder raw material is loaded into a graphite mold, and placed in a hot pressing furnace loading platform for rapid vacuum hot pressing treatment. During this process, a pressure of 10MPa is applied to the upper and lower ends of the graphite mold, the hot pressing temperature is 1000℃, the holding time is 10min, and the hot pressed blank is obtained after cooling.
[0091] The hot pressed blank and the grinding balls were put into a ball mill for ball milling at a ball-to-material ratio of 10:1 for 48 hours. The ball milled product was sieved to obtain a molybdenum powder product with a particle size distribution of 2 to 8 μm, which was recorded as molybdenum powder M4.
[0092] After testing, the specific surface area of molybdenum powder M4 is 2.08m 2 / g. The cross-sectional morphology was observed by FIB sectioning, and the interior of molybdenum powder M4 was a loose porous structure.
[0093] Embodiments 5 to 7
[0094] The molybdenum powder with high specific surface area was prepared by referring to the method of Example 1, except that the molybdenum powder raw material, hot pressing conditions or ball milling conditions were adjusted as shown in Table 1. The prepared molybdenum powder products were respectively recorded as molybdenum powder M5, molybdenum powder M6, and molybdenum powder M7.
[0095] The test shows that the specific surface areas of molybdenum powder M5 to molybdenum powder M7 are 2.45m 2 / g, 2.11m 2 / g, 2.25m 2 / g. The cross-sectional morphology was observed by FIB sectioning, and the interiors of molybdenum powders M5 to M7 were all loose and porous structures.
[0096] Comparative Example 1
[0097] Molybdenum powder was prepared by referring to the method of Example 1, except that the holding time in the hot pressing treatment was extended to 100 min. The obtained molybdenum powder product was recorded as molybdenum powder D1.
[0098] The specific surface area of molybdenum powder D1 is 0.72m 2 / g. The cross-sectional morphology was observed by FIB slicing. The results are as follows Figure 5 As shown in the figure, it can be seen that there is no loose structure inside the molybdenum powder D1.
[0099] Comparative Example 2
[0100] Molybdenum powder was prepared by referring to the method of Example 1, except that the heat treatment temperature in the hot pressing treatment was reduced to 800° C. The obtained molybdenum powder product was recorded as molybdenum powder D2.
[0101] The specific surface area of molybdenum powder D2 is 0.65m 2 / g. The cross-sectional morphology was observed by FIB slicing. The results are as follows Figure 6 As shown in the figure, it can be seen that there is no loose structure inside the molybdenum powder D2.
[0102] Comparative Example 3
[0103] Molybdenum powder was prepared by referring to the method of Example 1, except that the heat treatment temperature in the hot pressing treatment was increased to 1300° C., and the hardness of the obtained hot pressed blank was too high to be formed into powder by ball milling.
[0104] The hot pressed green sheet was sliced by FIB to observe the cross-sectional morphology. The results at different magnifications are as follows: Figure 7 and 8 As shown in the figure, it can be seen that the interior of the blank has been alloyed.
[0105] Comparative Example 4
[0106] Molybdenum powder was prepared by referring to the method of Example 1, except that the holding time in the hot pressing treatment was shortened to 3 minutes. The obtained molybdenum powder product was recorded as molybdenum powder D4.
[0107] According to the test, the specific surface area of molybdenum powder D4 is 1.11m 2 / g. The cross-sectional morphology was observed by FIB slicing. The results are as follows Fig. 9 As shown in the figure, it can be seen that pores have just begun to form inside the molybdenum powder D4.
[0108] Table 1
[0109]
[0110]
[0111] From Table 1, it can be seen that by comparing Examples 1-7 with Comparative Examples 1-4, the methods of Examples 1-7 can effectively increase the specific surface area of molybdenum powder, and the prepared molybdenum powder products have a loose structure inside, and their specific surface area is more than 3 times the specific surface area of the molybdenum powder raw material, which can significantly and efficiently increase the specific surface area of the molybdenum powder.
[0112] The following application examples are used to illustrate the metallized ceramic slurry of the present application and the metallized ceramic substrate formed by using the slurry.
[0113] Application Example 1
[0114] The solid powder and the organic binder are mixed evenly with an ink agitator to obtain a ceramic metallization slurry. The solid powder is composed of the molybdenum powder M1 prepared in Example 1 and oxides (composed of manganese oxide, aluminum oxide and silicon dioxide in a mass ratio of 1:1.5:0.8) in an amount of 75% and 25% by mass respectively; the organic binder is α-pinene alcohol and ethyl cellulose (in a mass ratio of 1:0.2), and the added mass is 35% of the mass of the solid powder.
[0115] The slurry was uniformly coated on the surface of the alumina ceramic substrate and sintered at 1450° C. for 8 h in a hydrogen atmosphere to obtain a metallized ceramic substrate with a transition layer (ie, sintered coating) having a thickness of 25 μm.
[0116] The cross section of the metallized ceramic substrate was characterized by SEM, and the results were as follows Figure 2As shown, it can be observed that the cross section is sintered densely (the lower layer is the ceramic substrate and the upper layer is the sintered coating).
[0117] Application Comparative Example 1
[0118] A metallized ceramic substrate was prepared by referring to the method of Application Example 1, except that the molybdenum powder D1 prepared in Comparative Example 1 was used to replace the molybdenum powder M1 in Example 1.
[0119] Application Example 2
[0120] The solid powder and the organic binder are mixed evenly with an ink agitator to obtain a ceramic metallization slurry. Among them, the solid powder is composed of molybdenum powder M2 and oxides (manganese oxide, aluminum oxide and silicon dioxide in a mass ratio of 1:1.2:0.7) with a mass ratio of 68% and 32% respectively; the organic binder is α-pinene alcohol and ethyl cellulose (mass ratio of 1:0.1), and the added mass is 30% of the mass of the solid powder.
[0121] The slurry was uniformly coated on the surface of the alumina ceramic substrate and sintered at 1500° C. for 8 h in a hydrogen atmosphere to obtain a metallized ceramic substrate with a transition layer thickness of 20 μm.
[0122] The cross section of the metallized ceramic substrate was characterized by SEM, and the results were as follows Figure 4 As shown, it can be observed that the cross section is sintered densely (the lower layer is the ceramic substrate and the upper layer is the sintered coating).
[0123] Test Case
[0124] The bonding strength between the transition layer on the metallized ceramic substrate prepared in Application Examples 1-2 and Application Comparative Example 1 and the ceramic substrate was tested.
[0125] Referring to GB-T 6400-2007, a universal testing machine was used to shear the specimen until it broke with a test shear speed of 15 mm / min to obtain the shear strength.
[0126] The test results are shown in Table 2.
[0127] Table 2
[0128] Serial number Molybdenum powder number Shear strength(MPa) Application Example 1 M1 99.57 Application Comparative Example 1 D1 39.70 Application Example 2 M2 98.95
[0129] It can be seen from Table 2 that, compared with the comparative example 1, the transition layers in the application examples 1 and 2 have higher bonding strength to the ceramic substrate.
[0130] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A method for preparing high specific area molybdenum powder, characterized in that, The method includes: (1) hot pressing treatment: placing a molybdenum powder raw material with a specific surface area of A1 in a mold, and hot pressing it at a temperature of 900 to 1100° C. for 5 to 30 minutes to obtain a hot pressed blank; (2) Crushing and pulverizing: The hot pressed blank is crushed and pulverized to obtain high specific area molybdenum powder with a specific surface area of A2, wherein A1<A2.
2. The method according to claim 1, characterized in that: The specific surface area A1 of the molybdenum powder raw material is 0.3 to 0.8 m 2 / g, the specific surface areas A2 and A1 of the high specific area molybdenum powder satisfy the following relationship: A2 / A1>3.
3. The method according to claim 1 or 2, characterized in that: The Fischer-Tropsch particle size of the molybdenum powder raw material is 20-500 nm, and the purity of the molybdenum powder raw material is ≥99%.
4. The method according to any one of claims 1 to 3, characterized in that: The heat pressing treatment is a vacuum heat pressing treatment, and the applied pressure is 5 to 60 MPa, preferably 10 to 50 MPa.
5. The method according to any one of claims 1 to 4, characterized in that: The crushing and pulverizing process is a ball milling process, the ball-to-material ratio is (5-100):1, and the ball milling time is 12-50 hours.
6. The method according to any one of claims 1 to 5, characterized in that: The method further includes: (3) Screening: Screening the product after the crushing and pulverizing process to obtain a high specific area molybdenum powder with a particle size distribution of 1 to 20 μm.
7. The method according to any one of claims 1 to 6, characterized in that: The specific surface area A2 of the high specific area molybdenum powder is 1.8 to 3 m 2 / g.
8. The high specific area molybdenum powder prepared by the method described in any one of claims 1 to 7.
9. A ceramic metallization slurry, characterized in that: It comprises solid powder and an organic binder, wherein the solid powder comprises molybdenum powder and oxide, and the molybdenum powder is the high specific area molybdenum powder as claimed in claim 8.
10. The ceramic metallization slurry according to claim 9, characterized in that: The oxide is at least one of manganese oxide, aluminum oxide and silicon dioxide, and the organic binder is pinene alcohol and / or ethyl cellulose; Preferably, in the solid powder, the mass content of the molybdenum powder is 65% to 85%, and the mass content of the oxide is 15% to 35%; Preferably, the organic binder is in an amount of 30 to 40 parts by weight relative to 100 parts by weight of the solid powder.
Citation Information
Patent Citations
Molybdenum powder and preparation method thereof
CN117324619A